Sovereignty and an Empty Purse : Banks and Politics in the Civil War - Hammond, Bray (Book collections on Project MUSE., 2014)
A sequel to his Pulitzer Prize-winning Banks and Politics in America from the Revolution to the Civil War, this book by Bray Hammond focuses on how Washington struggled financially to settle the Civil War and how its measures spurred the growth of federal government. Originally published in 1993. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while.